Pengaruh Stres Kerja, Pelatihan Kerja dan Budaya Kerja terhadap Kinerja Karyawan J&T Express Jawa Timur pada Drop Point J&T Wilayah Surabaya Utara - Juvie Ekanada B, (Manajemen Kreatif Jurnal, 2024)
This research aims to analyze work stress, job training, and work culture which influence the performance of J&T Express East Java, North Surabaya employees. This type of research is research with a quantitative approach. The population in this study were all employees of J&T Express East Java, North Surabaya. Determining the sample in the study used probability sampling using the Slovin formula so that the number of samples in this study was 80 employees. The data analysis method in this research uses SPSS analysis tools through validity, reliability, classical assumption tests, namely normality test, multicollinearity test, heteroscedasticity test, multiple linear regression, t test, F test and correlation and determination coefficients. The results of this research are known to be (1) The research results obtained tcount of 2.928 with a significance value of 0.005 <0.05, so Ho is rejected and H1 is accepted so that work stress (X1) influences employee performance (Y) 2. The research results obtained tcount of 4.676 with a value significance is 0.000 < 0.05, then Ho is rejected and H2 is accepted so that the job training variable (X2) has an effect on employee performance (Y). 3. The research results obtained a tcount of 0.533 with a significance value of 0.596 > 0.05, so Ho was accepted and H3 was rejected. So the work culture variable (X3) has no effect on employee performance (Y) 4. From the results of these calculations, Fcount is 29.174, which means Fcount is 29.174 > Ftable 2.730, so Ho is rejected and H4 is accepted. So the independent variables: Job Stress, Job Training and Work Culture simultaneously/together influence employee performance at J&T Express, East Java, North Surabaya Region.